Structural Characterization of the Symbiotically Important Low-Molecular-Weight Succinoglycan of Sinorhizobium meliloti - Wang, Lai-Xi (American Society for Microbiology, 1999)
The production of succinoglycan by Sinorhizobium meliloti Rm1021 is required for successful nodule invasion by the bacterium of its host plant, alfalfa. Rm1021 produces succinoglycan, an acidic exopolysaccharide composed of an octasaccharide repeating unit modified with acetyl, succinyl, and pyruvyl moieties, in both low- and high-molecular-weight forms. Low-molecular-weight (LMW) succinoglycan, previously thought to consist of monomers, trimers, and tetramers of the repeating unit, has been reported as being capable of promoting the formation of nitrogen-fixing nodules by succinoglycan-deficient derivatives of strain Rm1021. We have determined that the three size classes of LMW succinoglycan species are in fact monomers, dimers, and trimers of the repeating unit and that the trimer is the species active in promoting nodule invasion. A detailed structural analysis of the components of LMW succinoglycan by using various chromatographic techniques, along with nuclear magnetic resonance analyses, has revealed that there is considerable heterogeneity within the LMW succinoglycan oligomers in terms of noncarbohydrate substitutions, and we have determined the structural basis of this heterogeneity.